2018
DOI: 10.1016/s2352-4642(18)30273-6
|View full text |Cite
|
Sign up to set email alerts
|

Influence of maternal obesity on the association between common pregnancy complications and risk of childhood obesity: an individual participant data meta-analysis

Abstract: EU's Horizon 2020 research and innovation programme (LifeCycle Project).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
68
1
5

Year Published

2019
2019
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 113 publications
(76 citation statements)
references
References 38 publications
2
68
1
5
Order By: Relevance
“…There is evidence that both maternal BMI and GDM are independently associated with adverse pregnancy outcomes, with maternal pre‐pregnancy BMI having a stronger influence than GDM on foetal macrosomia, Caesarean section, pre‐eclampsia, and large for gestational age . By comparison, the observed positive associations between maternal GDM and childhood overweight and obesity could be largely explained by maternal pre‐pregnancy BMI . Therefore, the observed increased risk of childhood‐onset T1DM with maternal GDM should also be interpreted within this context.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…There is evidence that both maternal BMI and GDM are independently associated with adverse pregnancy outcomes, with maternal pre‐pregnancy BMI having a stronger influence than GDM on foetal macrosomia, Caesarean section, pre‐eclampsia, and large for gestational age . By comparison, the observed positive associations between maternal GDM and childhood overweight and obesity could be largely explained by maternal pre‐pregnancy BMI . Therefore, the observed increased risk of childhood‐onset T1DM with maternal GDM should also be interpreted within this context.…”
Section: Discussionsupporting
confidence: 92%
“…Thus, it is not surprising that both conditions share a number of common adverse maternal and offspring outcomes, which are also known to be risk factors for childhood‐onset T1DM. Similar to maternal overweight and obesity, maternal GDM is also associated with increased risks of high birthweight, preterm labour, pre‐eclampsia, Caesarean section, and childhood obesity (see Maternal overweight and obesity ). There is evidence that both maternal BMI and GDM are independently associated with adverse pregnancy outcomes, with maternal pre‐pregnancy BMI having a stronger influence than GDM on foetal macrosomia, Caesarean section, pre‐eclampsia, and large for gestational age .…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies suggested that obesity among parents is associated with obesity in children . Among those reports, a large scaled meta‐analysis, using individual data of prospective birth cohort in Europe and North America, reported that BMI of mothers is an important predictor of obesity in adolescence, rather than other pregnancy complications such as prenatal diabetes . Additionally, one study in Norway reported that girls were at a higher risk of the effect of obesity in mothers; however, the age reported for their study outcome was 7 years .…”
Section: Discussionmentioning
confidence: 99%
“…Epidemiological data from human catastrophes such as the Dutch famine (1944), the siege of Leningrad (1942Leningrad ( -1944, the great Chinese famine (1958)(1959)(1960)(1961), and the Överkalix study (1890-present) propose that changes in nutrient intake such as fasting or overnutrition during pregnancy and lactation are associated with metabolic and behavioral disorders in the offspring (Vaiserman, 2017). Maternal nutritional programing can influence offspring body weight, adiposity, and development of metabolic syndrome in diverse ways (Friedman, 2018;Patro Golab et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…For instance, nutritional programing adversely impacts both maternal and offspring health, increasing susceptibility to show metabolic abnormalities later in life such as obesity, dyslipidemia, type 2 diabetes (T2D) mellitus and hypertension, as well as behavioral disorders related to schizophrenia, autism, and compulsive eating (Shapiro et al, 2017;Friedman, 2018;Patro Golab et al, 2018;Derks et al, 2019).…”
Section: Introductionmentioning
confidence: 99%